Association mapping in multiple yam species (Dioscorea spp.) of quantitative trait loci for yield-related traits - Adejumobi, I.I.; Agre, A.P.; Adewumi, A.S.; Shonde, T.E.; Cipriano, I.M.; Komoy, J.; Adheka, J.G.; Onautshu, O.D. (Springer, 2023)
Background Yam (Dioscorea spp.) is multiple species with various ploidy levels and is considered as a cash crop in many producing areas. Phenotypic selection in yam improvement is a lengthy procedure. However, marker-assisted selection has proven to reduce the breeding cycle with enhanced selection efficiency.